Initial recruitment and establishment of vascular plants in relation to topographical variation in microsite conditions on a recently-deglaciated moraine on Ellesmere Island, high arctic Canada - Mori, Akira; Osono, Takashi; Iwasaki, Shogo; Uchida, Masaki; Kanda, Hiroshi (National Institute of Polar Research, 2006)
P(論文) We investigated the effects of topographical positions (moraine ridge, upper side slope and lower side slope) within a recently-deglaciated young moraine on initial recruitment and establishment of vascular plants. Compared with the moraine ridge, the upper slope had similar/higher abundance of vascular plants in terms of percent cover, frequency occurrence, species number, and density/biomass of a dominating species, Salix arctica. Establishment and growth of vascular plants are generally inhibited on unstable habitats; nevertheless, on this newly-formed moraine, every attribute measured for vascular plants implied a higher probability of vascular plant recruitment on the upper slope, where substrate is less stable than on the ridge. Further, the microsite with greater vascular plant abundance, S. arctica density and S. arctica aboveground/leaf biomass accumulated more organic materials regardless of topographical positions, and such an organic accumulation was deepest on the upper slope, suggesting that relatively-successful plant establishment occurs on this site. This is further supported by the S. arctica population structure, which implies a relatively-constant juvenile supply on the upper slope. Along a slope, unstable gravels easily slide down hill. This topographical process may cause large rock size and high surface cover by rocks on the lower slope. On the upper slope, the percent cover by rocks had therefore become smaller, leading to high cover by fine-grained sediments, which retain moisture favorable for germination and growth of vascular plants. This would enhance the emergence of pioneer vascular plant species, probably resulting in higher vascular plant abundance, density and biomass of S. arctica on the upper slope. This study suggests that during primary succession following deglaciation in the high arctic the upper slope of a newly-formed glacier moraine may be an important location for the initial recruitment and establishment of pioneer vascular plant species, such as S. arctica. ...